2013
DOI: 10.1016/j.mjafi.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene practices among health care workers (HCWs) in a tertiary care facility in Pune

Abstract: Inadequate compliance despite knowledge and false sense of security by alcohol based rubs was seen. A multi disciplinary, multifaceted approach is required to tackle issues of non-compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 13 publications
(11 reference statements)
3
28
2
1
Order By: Relevance
“…This finding is similar to the findings in other studies which have reported an increased use of quick method of HH (alcohol-based hand sanitizers) in health care settings especially in high demand situations and in crowded areas of hospitals (Heqde, Andrade, & Bhat, 2006;Hugonnet, Perneger, & Pittet, 2002). A study conducted in India showed that 85% HCWs considered hand rubbing with alcohol-based rubs to be more rapid and less time-consuming than HW with soap and water (Anargh et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is similar to the findings in other studies which have reported an increased use of quick method of HH (alcohol-based hand sanitizers) in health care settings especially in high demand situations and in crowded areas of hospitals (Heqde, Andrade, & Bhat, 2006;Hugonnet, Perneger, & Pittet, 2002). A study conducted in India showed that 85% HCWs considered hand rubbing with alcohol-based rubs to be more rapid and less time-consuming than HW with soap and water (Anargh et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…A self-administer questionnaire was developed from previous studies conducted in Nepal, India, and Nigeria (Anargh, Singh, Kulkarni, Katwal, & Mahen, 2013;Maheshwori et al, 2014;Timothy & Ifeoma, 2013 Pilot testing was done among 20 HCWs at College of Medical Sciences Teaching Hospital, Chitwan, Nepal. The respondents included in the pilot testing were excluded from the study.…”
Section: Data Collectionmentioning
confidence: 99%
“…These findings indicate that health care worker needs more rigorous, comprehensive, and regular education and training on hand hygiene and infection prevention to the HCWs. A study conducted in India showed that 85% HCWs considered hand rubbing with alcohol-based rubs to be more rapid and less time-consuming than hand wash with soap and water (Anargh et al, 2013) which is similar to our finding (82%).…”
Section: Resultssupporting
confidence: 90%
“…Finally, hand hygiene policy was a motivator for the participants to engage in more vigilant hand hygiene 4 . Congruent with the identified facilitators, the main barrier to performing hand hygiene was the non-accessibility of handwashing sinks and alcohol-based hand rub facilities, which was a common finding in previous studies 49,50 . Interestingly, in the present study, the issue of co-morbidity was cited as a barrier due to concerns about its contribution to HAIs, suggesting that a motivation to comply with hand hygiene behaviour was in conflict with patient factors.…”
Section: Discussionmentioning
confidence: 88%